The UniCAR system: a modular CAR T cell approach to improve the safety of CAR T cells - Bachmann, Michael (Immunology letters, 2019)
The idea to eliminate tumor cells via our own immune system is more than a hundred years old. However, a real break through came first with the development of check point inhibitors, bispecific antibodies (bsAbs) and T cells genetically modified to express Chimeric Antigen Receptors (CARs). Eventhough the clinical application of T cells equipped with CARs can lead to a complete remission, unfortunately, their application can also cause severe or even life threatening side effects as their activity can no more be adjusted once given to the patient. For targeting of tumor cells expressing tumor associated antigens (TAAs) which are not limited to tumor cells but also accessible on healthy tissues CAR T cells should not be permanently in a killing mode but be equipped with some kind of a switch whereby the activity of CAR T cells can reversely be turned "on and off ". Moreover, in case of cytokine release syndrome (CRS), tumor lysis syndrome (TLS), or other deadly side effects the possibility of an emergency shut down of the CAR T cell activity should exist. Modular CAR variants such as the UniCAR system may fulfill these requirements.
Gesehen am 31.07.2019